Manajemen Rekrutmen Guru Pendidikan Agama Islam Di Sekolah Menengah Atas Islam Terpadu Nur Hidayah Surakarta Kecamatan Kartasura Kabupaten Sukoharjo - Arif Supriyadi (Jurnal Hadratul Madaniyah, 2017)
This research used a descriptive qualitative approach. The implementation of this research was four months beginning from January until April 2014. The object of this research was SMAIT Nur Hidayah of Surakarta. The subject of this research was recruitment teams, including of recruitment chief, the vice of recruitment chief, and candidate of new teacher’s assessors. The informants of this research were chief of the institution, Principal, teachers, and administration officers. Data collecting method applied observation, interview, and documentation, while, data validation techniques used triangulation method and sources. The method of data analysis used interactive model consisting of data collecting, reduction, performing, and verification. Research results show that recruitment management of new teachers in SMA IT Nur Hidayah of Surakarta, Kartasura district, Sukoharjo regency provides excellent quality of new teachers. The purpose of recruitment can be achieved because recruitment management of new teachers has been done well, including a) planning of new teacher’s recruitment by analyzing of teacher’s needs; b) organizing has been done by the making a particular team in new teacher’s recruitment; c) executing of recruitment including socialization announcement of new teacher’s acceptance, administration selection, writing, interview, reading and memorizing of Qur’an, and microteaching tests; d) controlling of recruitment team has been done by the institution party and Principle of SMA IT Nur Hidayah Surakarta in executing of new teacher’s recruitment. Teacher’s recruitment management by school party has been done effectively. In this matter, it can be seen in the new teacher’s recruitment process with has been done by the recruitment team selectively and systematically. Therefore, it provides qualified teachers.